Comment on: Emergence of the invasive malaria vector Anopheles stephensi in Khartoum State, Central Sudan - Jan Kolaczinski (BMC, 2021)
Abstract This letter comments on the article “Emergence of the invasive malaria vector Anopheles stephensi in Khartoum State, Central Sudan” published in Parasites and Vectors 2021, 14:511. Here we aim of provide a response to this paper in the broader context of the invasion and spread of An. stephensi in the Horn of Africa, and the required response to it. We agree with the authors that the arrival of this invasive vector in Khartoum State is of high public health concern. Equally concerning, however, we found that the detection of the vector by the authors in 2018 seemingly took 3 years to communicate to the Ministry of Health and World Health Organization (WHO), and was reliant on an academic journal. We consider that this short report sets a poor example of how public health threats should be reported. Suitable communication alternatives to alert public health authorities to such threats have been put in place by the WHO and its Member States, and are well known to at least some of the authors of the short report. We would like to encourage all readers not to follow the example of Ahmed et al. but instead act as responsible public health professionals by drawing on the established reporting mechanisms and escalate potential threats as soon as they are identified. Graphical Abstract